Exploring teacher’s lived experiences cultivating character education through Aqidatul Awwam nadhoman within multiple intelligences framework - Mufarochah, Siti; Sa’diyah, I’in Khalimatus; Romanti, Aulia Difaeni (Proceeding of International Conference on Islamic Education (ICIED), 2025)
Teachers have the task of supporting the improvement of character education values ​​to form students who have good personalities and morals, of course by using various approaches including nadhoman Aqidatul Awwam. The purpose of this study is a deep understanding of the meaning and experience of teachers in cultivating the value of character education through nadhoman Aqidatul Awwam and identifying the practice of teacher experience towards deeper pedagogical competence. Qualitative with a phenomenological approach is the method in this study with the results in the form of teachers using nadhoman Aqidatul Awwam as a means of instilling positive values ​​of faith, character in children by using strategies that integrate with Multiple Intelligences, especially in Linguistic, Musical, Interpersonal and Existential intelligence. Although various challenges are experienced in the process of habituating character education in schools. The conclusion in this study is that character education can be instilled by teachers with a multiple intelligences-based approach with nadhoman Aqidatul Awwam as a means